Does gender influence perioperative complications in transforaminal lumbar interbody fusion (TLIF) technique? A prospective multicentric cohort study - Hayder Qatran Raheem, MD; Ghazwan Abdulla Hasan, MD; Reda Ali Sheta, MD (Interdisciplinary Neurosurgery, 2020)
Objectives: We aimed to assess the effect of gender on the rate of perioperative and early postoperative complications after mono segment lumbar spine fusion using open transforaminal lumbar interbody fusion (TLIF) technique. Material and methods: We conducted this prospective multicentric cohort study between January 2015 and February 2019. We included patients with degenerative disc disease, spondylolisthesis, primary or recurrent disc prolapse, and spinal stenosis. After the failure of other conservative measures, all patients underwent mono segment interbody fusion using an open TLIF approach. Patients were classified based on their biologically assigned gender. We used the SPSS software version 25 for statistical analysis. Results: We included a total of 335 patients (147 male and 188 female). Of them, a percentage of 55.8% aged between 30 and 50 years. The level of surgery was L4-S1 in 87.1% of the included cases. The female patients had longer operative time, more blood loss, and longer hospital stays than the male patients 110.9 vs. 104.6, 471.6 ccs vs. 441.8 ccs, 3.31 days vs. 2.12 days; p = 0.01, p = 0.23, and p < 0.001, respectively. Of the 54 reported complications, 38 were with female patients (p = 0.02). The most-reported complications were as follows: dural tear in 16 cases (5 male and 11 female), traction neuritis in 15 cases (4 male and 11 female), and wound infection in 9 cases (3 male and 6 female). Conclusion: Our study showed patients' gender directly correlated with their operative time, length of hospital stay, as well as the rate of complication, with the female variable showing a trend of notable increase on all aforementioned items after mono segment TLIF surgery.